Forward view: advancing health library and knowledge services in England. (10th January 2018) - Lacey Bryant, Sue; Bingham, Helen; Carlyle, Ruth; Day, Alison; Ferguson, Linda; Stewart, David
Abstract: This article is the fourth in a series on New Directions. The National Health Service is under pressure, challenged to meet the needs of an ageing population, whilst striving to improve standards and ensure decision making is underpinned by evidence. Health Education England is steering a new course for NHS library and knowledge services in England to ensure access to knowledge and evidence for all decision makers. Knowledge for Healthcare calls for service transformation, role redesign, greater coordination and collaboration. To meet user expectations, health libraries must achieve sustainable, affordable access to digital content. Traditional tasks will progressively become mechanised. Alongside supporting learners, NHS librarians and knowledge specialists will take a greater role as knowledge brokers, delivering business critical services. They will support the NHS workforce to signpost patients and the public to high‐quality information. There is a need for greater efficiency and effectiveness through greater co‐operation and service mergers. Evaluation of service quality will focus more on outcomes, less on counting. These changes require an agile workforce, fit for the future. There is a bright future in which librarians' expertise is used to mobilise evidence, manage and share knowledge, support patients, carers and families, optimise technology and social media and provide a keystone for improved patient care and safety.